REKOMENDASI KELAYAKAN PEMINJAMAN PADA KOPERASI DENGAN METODE TSUKAMOTO - lumban gaol, frenky lambas; Handoko, Koko (Computer and Science Industrial Engineering (COMASIE), 2022)
Technological developments from time to time are very rapid starting from the environment and technology where all needs are easily obtained both face-to-face and indirectly, namely through technology media. . Cooperatives are institutions or business entities within the community that are owned and operated by their members to fulfill common interests in the economic field. Cooperatives have a goal to improve the standard of living of cooperative members, help the lives of cooperative members in economic terms and become one of the savings and loan services. Fuzzy logic is one of the logics that is able to determine and produce fairer decisions and fuzzy logic is an improvement from Boolean logic which deals with the concept of partial logic. The Tsukamoto method is a method used to assist in providing recommendations quickly, precisely and accurately. The Tsukamoto method is the most monotonous of all methods in fuzzy logic. The way this method works is by assigning unequivocal values ​​to all data and finding the best average of each possibility as the final result..